Immunogenicity and immune persistence of Zagreb 2-1-1 regimen of rabies vaccine in Chinese healthy individuals: A randomized, parallel-controlled of homologous vaccine with different immune procedure study - Li Li; Jingyi Xu; Jiao Zhang; Fang Wang; Jianlin Cai; Liqing Yang; Zhenggang Zhu; Yunhua Bai; Bin Jia; Jianxin Ma; Nianmin Shi; Shuping Li (Taylor & Francis Group, 2024)
This study was a randomized, parallel-controlled of homologous vaccines with different immune procedure research to evaluate the immunogenicity and immune persistence of Zagreb 2-1-1 regimen of rabies vaccine in Chinese healthy individuals. 240 subjects aged ≤ 20、21-50、≥51 y were randomly divided into 2 groups (1:1), Zagreb 2-1-1 regimen receivers as experimental group and Essen 5 regimen receivers as controlled group. Researchers collected venous blood of each subject before vaccine injection and on the day 7, 14, 42, 180, 365 after first dose. The immunogenicity and immune persistence was assessed by neutralizing antibody. The positive rate of neutralizing antibody in experimental group was 14.53% on the 7th day, and raised to 100% on the 14th day. It showed no significant difference between experimental and controlled group (P>0.05). Either in experimental or controlled group, GMC of neutralizing antibody was up to the peak on the 14th day, and it showed no significant difference between two groups (P>0.05). On the 42nd day, the antibody positive rate remained 100% with both Zagreb 2-1-1 and Essen 5 regimens, and the GMC of antibodies also remained high level. Then, on the 180th and 365th day with both regimens, the GMC of antibodies dropped dramatically, although it remained above the protective level of 0.5 IU/ml, the positive rates dropped to 84.40% and 84.11% (on the 180th day), and 61.29% and 58.62% (on the 365th day). Rabies vaccine injected by Zagreb 2-1-1 regimen can produce neutralizing antibody fastly and perdurably.Registration: ClinicalTrials.gov #NCT01821911and NCT01827917